Urban sustainability-land availability for highway development in Malaysia - Omar, Ismail; Md. Yusof, Aminah; Zaukani, Fahmi Arif Zifa (2003)
The proposal of the East Coast Highway, connecting the West Coast to East Coast of Peninsular Malaysia was an effort undertaken by the government to provide infrastructure to better accessibility, hence, helps sustain the economic growth of the country. The purpose of the highway is to shorten the traveling time, and, thus boost the economic development of the States involved. However, the initial proposal of the highway in 1994 was postponed until the first work starts at the end of 2000. The long delay period is caused by various constraints in negotiation, acquisition of land and construction stages. The study seeks to review literatures on the provision of infrastructure with special reference to the process and procedure of land acquisitions and valuation for compensation purposes. Secondary data is gathered from public and private valuation reports on landtaken and then compared to the awards of compensation paid to the affected landowners using statistical analysis. In the end, it was revealed that there are differences in the valuation for compensation between public and private valuation that had created dispute on the amount of compensation of the value of land taken. There seems to be slightly different between the public valuation and value awarded to the affected landowners. In contrast, the private valuation seems generally disregarded. This indicates the practical aspect and applicability of the present code of land compensation to ensure the way to avoid delays in developing highway and providing necessary infrastructure to the people.